THE INFLUENCE OF DIFFERENT PACKAGING MATERIALS ON QUALITY OF PANGASIUS CATFISH DENDENG (Pangasius hypopthalmus) STORED AT ROOM TEMPERATURE - Desmelati Desmelati; Suparmi Suparmi; Alvian Dinata (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
The objective of this research was to determine the quality changes ofpangasius catfish dendeng packaged in a plastic bag of high density polyethylene(HDPE), low density polyethylene (LDPE) and aluminum foil during roomtemperature storage. Pangasius catfish weighing 250 – 300 each was taken from afish market in Pekanbaru. The fish was processed for dendeng; and the fishdendeng was packaged in a plastic bag of HDPE, LDPE and alumunium foil; andstored at room temperature for 35 days. The fish dendeng was evaluated forsensory value, moisture, fat and total mould every 0, 7, 14, 21, 28 and 35 days.The results showed that the quality of fish dendeng packaged in HDPE and LDPEdecreased faster than that packaged in aluminum foil. Sensory value packaged inHDPE, LDPE and alumunium foil at initial to the end of stroage was 6,85 – 5,89;6,88 – 5,64; 7,26 – 5,92. Moisture content, fat and total mould of fish dendengpackaged in aluminum foil during storage was 6,60 -11,40 %; 7,30 – 1,70 %;4,0 x103 – 5,9 x 104 respectively; dendeng packaged in HDPE was 6,90 - 11,70 %;9,60 – 1,80 %; 4,1 x 102 – 7,2 x 104 respectively; and dendeng packed in LDPEwas 7,60 - 11,90 %;6,90 – 1,90 %; 3,8 x 102 – 3,9 x 105 respectively.Keywords : Pangasius catfish dendeng, high density polyethylene, low density polyethylene and aluminum foil, sensory evaluation, moisture, fat, mould.